1997
DOI: 10.1021/es970151a
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Fate of Carbonyl Oxidation Products Originating from α-Pinene and Δ3-Carene:  Determination of Rate of Reaction with OH and NO3 Radicals, UV Absorption Cross Sections, and Vapor Pressures

Abstract: Large yields of dicarbonyl compounds have been found in the atmospheric oxidation of R-pinene and ∆ 3 -carene. These terpenes are emitted in large quantities by biogenic sources, and it is important to know the fate of their reaction products. In this investigation, ultraviolet and infrared absorption cross sections, vapor pressures, and rate coefficients for hydroxyl and nitrate radical reactions have been determined for the main product in each case, i.e., 3-acetyl-2,2-dimethylcyclobutaneacetaldehyde (pinona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
145
2
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 26 publications
15
145
2
5
Order By: Relevance
“…While closer to the expected range this value is still low. On the other hand, applying the vapour pressure recently estimated by Tillmann et al (2009), which is about two to three orders of magnitude smaller than the value reported by Hallquist et al (1997), the results are almost consistent with the two product approach. However, since the vapour pressure of pinonaldehyde still seems to have substantial uncertainty this compound was not included explicitly into the model analysis presented in this paper.…”
Section: Parameters Of the Two Effective Soa Forming Products (Proxies)supporting
confidence: 83%
See 3 more Smart Citations
“…While closer to the expected range this value is still low. On the other hand, applying the vapour pressure recently estimated by Tillmann et al (2009), which is about two to three orders of magnitude smaller than the value reported by Hallquist et al (1997), the results are almost consistent with the two product approach. However, since the vapour pressure of pinonaldehyde still seems to have substantial uncertainty this compound was not included explicitly into the model analysis presented in this paper.…”
Section: Parameters Of the Two Effective Soa Forming Products (Proxies)supporting
confidence: 83%
“…Using the PTR-MS measurements we could indeed observe an increasing partitioning of pinonaldehyde into the condensed phase with decreasing temperature and hence a larger contribution to the semivolatile SOA fraction (Tillmann et al, 2009). Including pinonaldehyde in our model analysis with the molar yields determined by Tillmann et al (2009) but relying on the vapour pressure parameterisation derived by Hallquist et al (1997) leads to a stronger temperature dependence of the vapour pressure of the remaining effective semivolatile SOA component as reflected by an increase of the evaporation enthalpy to about 34 kJ mol −1 . While closer to the expected range this value is still low.…”
Section: Parameters Of the Two Effective Soa Forming Products (Proxies)mentioning
confidence: 99%
See 2 more Smart Citations
“…The vapour pressures of its oxidation products range from 10 −2 torr to 10 −7 torr (Hallquist et al, 1997;Hoffmann et al, 1997;Bilde and Pandis, 2001). The least volatile of these products can enter the aerosol phase and form secondary organic aerosol (SOA) (Kanakidou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%